Personality Variables and Human Resources Development in Nigeria (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2011)
This research analyzed the effects of personality variables on human resourcesdevelopment. Trait theory of personality and its influences on behavioural (personality)tendencies formed the conceptual background. Consequently, personal variables likeintellectual abilities, and physical abilities, as well as social variables emerged as the majordeterminants of human resources development. In order to cope with the dynamism anddiversity of most modern work demand, it is necessary to develop human resources towardscoping with “temporariness” (flux of changes). A number of factors were identified asbeing relevant implications of effective human resources development. These werereduction in lay-off, skills improvements, and work adaptation. However, the problemsmilitating against effective human resources development in Nigeria were poorly definedpersonnel development programme, lack of practice of acquired skills, incompetenttrainers, lack of feedback, and non-utilization of experts like psychologists. Consequently,it is recommended that these problems could be solved by ensuring that individuals aretrained to be adaptive to the inevitable changing work requirements. Again, humanresources development programme should be objectively focused, so as to avoid it beingconverted into a holiday occasion.
Keywords: Personality-variables, Human-resources, Development, Nigeria